The Gravitational Wave Symphony of Structure Formation: Overview. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Lazio, T. Joseph W.; Burke-Spolaor, Sarah
Abstract : This Focus Meeting was designed to lie at the scientific intersection of structure formation and gravitational wave studies. In broad-strokes terms, binary supermassive black holes (BSMBHs) and cosmic strings may both play a central role in shaping the Universe as we know it.